Author Correction: Financial Incentives for Covid-19 Vaccines in a Rural Low-Resource Setting: A Cluster-Randomized Trial (Nature Medicine, 2023 29 12 (3193-3202), 10.1038/S41591-023-02670-4) - Mayol-Miranda, A (Nature Research, 2024)
Correction to: Nature Medicinehttps://doi.org/10.1038/s41591-023-02670-4, published online 27 November 2023. In the version of the article initially published, there was an error in the “Trial design, eligibility, randomization and recruitment” section: the sentence now reading “…the detailed protocol was included in the pre-registration and is available at https://doi.org/10.7910/DVN/X5MBHP” had the wrong link. This has now been corrected in the HTML and PDF versions of the article. © The Author(s) 2023.